A Comprehensive Review Towards Libyan Smart Cities - Ibrahem Alsharif; Hamza Emhemed Hebrisha; Abdussalam Ali Ahmed (African Journal of Advanced Pure and Applied Sciences, 2023)
Urban regions that make use of cutting-edge technology to improve resident quality of life and streamline city operations for sustainable cities by employing Information and Communication Technologies (ICTs) are known as Smart Cities (SCs). For effective and sustainable urban planning, transportation, energy management, and public services, the idea of the SC integrates a variety of technologies, including the Internet of Things (IoT), big data analysis, and Artificial Intelligence (AI). By increasing healthcare services, promoting energy efficiency, lowering traffic congestion, and allowing citizens to actively participate in civic decision-making processes, smart cities seek to make their environments more liveable and resilient. This article highlights the importance of smart cities as a means to address the challenges of urbanization and promote sustainable development in the 21st century in southern region of Libya. This article is considered as a comprehensive study for proving solution of the challenges in the field. A total of 30 publications are arranged and appended for quick referencing.